Problems in the planning of the organization and control of global marketing operations - Telaumbanua Diamond (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
This research discusses organizational planning and control of global marketing operations in the context of Company (G), an information technology company with marketing operations in Indonesia. This research data illustrates how the company manages organizational planning and control of its global marketing operations. Using qualitative research methods, using a literature study approach. This research obtains an in-depth understanding of how Company (G) plans and controls its global marketing operations. The research results show that this company has a matrix organizational structure that allows coordination between global and local marketing teams, as well as policy adjustments to local marketing strategies according to local market needs and preferences. The use of integrated operational control systems and information technology is key in monitoring and managing the company's global marketing performance. However, Company (G) is also faced with various challenges, including coordination between global and local teams, adapting marketing strategies to different local needs, human resource management, compliance with local regulations, and risk management. By considering these challenges and leveraging the advantages of information technology, Company (G) can improve its global marketing performance and